2015
DOI: 10.3746/pnf.2015.20.4.230
|View full text |Cite
|
Sign up to set email alerts
|

Microalgal Oil Supplementation Has an Anti-Obesity Effect in C57BL/6J Mice Fed a High Fat Diet

Abstract: This study investigated the impact of microalgal oil (MO) on body weight management in C57BL/6J mice. Obesity was induced for 8 weeks and animals were orally supplemented with the following for 8 additional weeks: beef tallow (BT), corn oil, fish oil (FO), microalgal oil (MO), or none, as a high fat diet control group (HD). A normal control group was fed with a normal diet. After completing the experiment, the FO and MO groups showed significant decreases in body weight gain, epididymal fat pad weights, serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 42 publications
(45 reference statements)
4
7
0
Order By: Relevance
“…In the present study, HF diet induced hyperleptinemia, while supplementation with P. tricornutum decreased the leptin level. This is consistent with the results of Yook et al, who showed a significant decrease in leptin plasma concentration, after eight weeks of treatment, in C57BL/6J mice fed a HF diet supplemented with Aurantiochytrium microalgal oil as a source of n-3 LC-PUFA [74]. Thus, n-3 LC-PUFA could be a potential agent against hyperleptinemia.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, HF diet induced hyperleptinemia, while supplementation with P. tricornutum decreased the leptin level. This is consistent with the results of Yook et al, who showed a significant decrease in leptin plasma concentration, after eight weeks of treatment, in C57BL/6J mice fed a HF diet supplemented with Aurantiochytrium microalgal oil as a source of n-3 LC-PUFA [74]. Thus, n-3 LC-PUFA could be a potential agent against hyperleptinemia.…”
Section: Discussionsupporting
confidence: 91%
“…At the end of week 10, insulin level of rats fed HFFD were higher than normal control. This result was the same as some researches, who stated that insulin concentrations were higher in the rats fed high fat diet compared to control [34][35][36][37][38][39], although their results were slightly different. Le et al said that high fructose diet in offspring of type 2 diabetic patients increased fasting plasma concentration of insulin [40].…”
Section: Discussionsupporting
confidence: 89%
“…T. lutea supplementation, rich in DHA, restored plasma leptin level in HF-fed Wistar rats. The study conducted by Yook et al [ 76 ] showed a leptinemia decrease after eight weeks of treatment in HF-fed C57BL/6 J mice supplemented with Aurantiochytrium microalga oil rich in DHA.…”
Section: Discussionmentioning
confidence: 99%
“…As well as other microalga species, T. lutea could have an anti-diabetic activity due to its high levels of bioactive molecules such as DHA and fucoxanthin [ 17 , 53 , 78 , 79 , 80 ]. Thus, the study of Yook et al [ 76 ] showed preventive effects of Aurantiochytrium sp. microalga oil (rich in n-3 PUFA, DHA) against hyperinsulinemia in C57BL/6 J mice submitted to a hyperlipidic diet, suggesting the beneficial effects of n-3 LC-PUFA, and particularly DHA, in the improvement of insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%